COSCA project description: COSCA working paper, No. 1 - Nweke, F.I. (1988)
The general objective of the Collaborative Study of Cassava in Africa (COSCA) is, to improve the relevance and impact of agricultural research on cassava by international agricultural research centres (!ARC) and national agricultural research systems (NARS) in Africa in order to take full advantage of the potential of cassava in increasing food production and incomes in Africa. The countries participating are Cote d'lvoire, Ghana, Nigeria, Zaire, Uganda and Tanzania. The major consideration in the choice of these countries is that they represent the important cassava zones of the continent and provide a wide range of ecological and socio-economic conditions. COSCA has adopted a systems approach, with a multi-disciplinary team, in order to collect information on cassava within the context of African farming and food systems. Not only will information be collected on production, processing, marketing and consumption of cassava, but similar information will be collected on other crops which are grown or consumed in the same fanning and food systems. The Collaborative Study of Cassava in Africa will be conducted in three phases: Phase I will involve a broad characterization of the cassava producing zones. Information will be collected by group interviews at the village level and by key informant interviews at the institutional level. Phase II will involve characterization of individual production, processing, marketing and consumption units. The information will be collected on single visits and collection methods will include direct observation, field measurements, and individualized interviews. Phase III is an extension of Phase II, but involves more intensive surveys with repeated interview visits in order to collect information on seasonal variables. These components of COSCA will be integrated into one study for data collection and analysis. Integration is assured at the data collection stage through the sampling process. Phase II of the survey Will be conducted on a subsample of Phase I sites; and Phase III will be conducted on subsamples of Phase II. During the analysis, the study will be further integrated, since each hypothesis will be tested with information collected at different phases and on different components. The three phases have been spread over a 4-year time frame (1988 -1992). After each phase is completed the output will be disseminated through a working paper series, research reports, journal articles, books and conference proceedings, in particular the triennial symposia of the African Branch of the International Society of Tropical Root Crops.